THE APPLICATION OF GRADUAL CHUNKING TECHNIQUE IN MANAGING STUDENTS’ ACADEMIC PROCRASTINATION: A PHENOMENOLOGICAL STUDY - Aisah, Siti; Setyowati, Rini (CV. TOTUS TUUS, 2026)
This study aimed to explore students’ experiences in applying the gradual chunking technique to manage academic procrastination. The study employed a qualitative phenomenological design to understand the subjective meanings constructed by students when dealing with the tendency to delay academic tasks. Data were collected through semi-structured interviews with students in the Islamic Guidance and Counseling Education Program at Universitas Pelita Bangsa who had experienced academic procrastination and had applied gradual chunking in completing academic assignments. The data were analyzed thematically with the support of NVivo through data reduction, coding, categorization, theme development, and verification. The findings indicate that academic procrastination emerges from the interaction of internal and external factors. Internal factors include negative perceptions of academic tasks, academic anxiety, perfectionism, weak time management, and physical fatigue. External factors include social media distraction, heavy task loads, closely spaced deadlines, and social and academic dynamics. The application of gradual chunking was perceived to help students initiate tasks, reduce feelings of being overwhelmed, improve focus, and strengthen self-regulation and self-efficacy during task completion. These findings suggest that gradual chunking has strong potential as an academic support strategy for helping students manage procrastinatory behavior.